Development of some transgenic rice lines containing the herbicide resistance gene BAR and study on inheritance of this BAR gene up to the T2 generation - Ho, Nguyen Huu (Academia Journal of Biology, 2014)
Development of some transgenic rice lines containing the herbicide resistance gene BAR and study on inheritance of this BAR gene up to the T2 generation